Comparative genomic analysis of Staphylococcus aureus CC80 strains. (c2015) - Bilen, Melhem E. (2016)
Staphylococcus aureus is a highly adaptive and versatile gram-positive bacterium and is considered one of the most isolated human pathogens and the most common cause of skin and soft tissue infections (SSTIs). The ongoing evolution of antimicrobial resistance namely the particularly methicillin-resistant strains of S. aureus (MRSA) has complicated the treatment of infections with such isolates. Global transmission of MRSA has been linked to international travel. However, in countries with a high prevalence of MRSA, imported cases are not easily distinguished from the domestic background prevalence. In this study we have selected ST80 MRSA strains isolated from clinical samples from Lebanon and Jordan for genome sequencing. DNA extracted from all isolates was prepared for sequencing, pooled together and run on Illumina MiSeq for paired-end 250-bp sequencing. Those isolates, found to be ST80, carried several virulence factors, namely PVL that causes a wide variety of diseases such as skin and mucosal lesions including necrotic hemorrhagic pneumonia. Additionally, intracellular adhesion proteins and clumping factors involved in biofilm formation and adhesion respectively were identified. Fibronectin binding proteins that play a role in invasion were expressed in all of our isolates. Moreover, exfoliative toxin, eta, which is the causative agent of staphylococcal scalded skin syndrome, was also detected. Nevertheless, different plasmids were identified in those isolates carrying several resistance genes towards Tetracyclines and Beta-lactams. Also, some isolates were shown to be resistant towards Lincosamide, Straptogramin and Macrolides. Finally, integrated phages, such as phi7401PVL and JS01 were identified in most of the isolates along with several CRISPR sequences that can be used in targeted therapies. Knowledge of epidemic MRSA clones can help in the development of effective strategies to aid in optimizing treatment, and revealing the mode of pathogenicity. The detection of rare SCCmec cassettes along with rare combination of toxin encoding genes, resistance factors and other virulence determinants could be indicative of MRSA clones being imported and warrants further studies to better understand and deal with such strains.